THE ANALSIS OF SECOND YEAR STUDENTS’ ABILITY IN USING SCANNING TECHNIQUE IN READING AT ENGLISH DEPARTMENT OF UNIVERSITA NEGERI PADANG - Annisa Iman Sari; Jufri Jufri; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
This research is aimed to analyze students’ ability in using scanning techniques in reading text at second year of English Department students at Universitas Negeri Padang. The population of this research was whole population of K2-16 class of English Department. The instrument of the research was reading test consist of eight texts by using scanning technique. Students were asked to answer 30 reading questions within the predetermined time in each text which had been calculated with Word per Minute (WPM) formula. The result of the data analysis shows; the average score of students in identifying statistic/amount/quality is quite good, the average score of students in identifying date/time is good, the average score of students in identifying definition is very good, the average score of students in identifying reason/cause is poor, in identifying name/place is poor, in identifying location/position is more than enough, the average score of students in identifying characteristic is enough, and the average score of students in identifying process is poor. Moreover, the students’ average score for the whole reading test was more than enough.